1996
DOI: 10.1002/hep.510230501
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of antibody to hepatitis C virus envelope 2 glycoprotein in patients with chronic hepatitis C virus infection

Abstract: The significance of circulating antibody to hepatitis C HCV E1 corresponds to the pestiviral gp33/gp25 envevirus (HCV) envelope glycoprotein 2 (E2)/nonstructural lope glycoprotein and the flaviviral envelope protein protein 1 (NS1) glycoprotein was studied in 83 patients (M/E), whereas E2/NS1 corresponds to the pestiviral with chronic HCV infection diagnosed by polymerase gp53/gp55 envelope glycoprotein and the flaviviral chain reaction (PCR). E2/NS1 antibody was quantita-NS1. 1 Based on the greater homology b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
13
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
4
13
0
Order By: Relevance
“…38 to the putative epitopes are detected in the cryoprecipitate and in the kidney biopsies of the same patients, confirming The role of cryoproteins in the pathogenesis of glomerulonephritis is suggested by the finding of IgM, IgG, and C3 that these antibodies have little or no neutralizing potential. 33 The same picture was found for nucleocapsid antigen, fraction at the sites of glomerular damage with the same distribution as the viral proteins. It can be argued that intrain that all patients displaying c22-3 Ag in the tissue had antic22-3 antibodies in the cryoprecipitates.…”
Section: Fig 3 Features Of Hcv-related Proteins In Tubulo-interstitsupporting
confidence: 59%
“…38 to the putative epitopes are detected in the cryoprecipitate and in the kidney biopsies of the same patients, confirming The role of cryoproteins in the pathogenesis of glomerulonephritis is suggested by the finding of IgM, IgG, and C3 that these antibodies have little or no neutralizing potential. 33 The same picture was found for nucleocapsid antigen, fraction at the sites of glomerular damage with the same distribution as the viral proteins. It can be argued that intrain that all patients displaying c22-3 Ag in the tissue had antic22-3 antibodies in the cryoprecipitates.…”
Section: Fig 3 Features Of Hcv-related Proteins In Tubulo-interstitsupporting
confidence: 59%
“…A specific cell-binding assay developed by Rosa et al [6] showed that the ability to neutralize binding of E2 glycoprotein derived from the HCV-1a strain is distributed equally among sera from persons infected by HCV genotypes 1, 2, and 3. These observations raise a possibility that such a cross-reactive anti-E2 antibody, which is prevalent among infected persons, could be protective against HCV infection.While some reports [2][3][4][5] have shown a high prevalence of anti-E2 antibodies in HCV-infected persons, a few surveys [7,8] found a much lower prevalence. This divergence of results is thought to arise from a difference in the conformation of the E2 protein utilized in the antibody detection system; some researchers [3-5] used glycosylated undenatured E2 protein, but others [7, 8] used nonglycosylated or denatured protein.…”
mentioning
confidence: 91%
“…While some reports [2][3][4][5] have shown a high prevalence of anti-E2 antibodies in HCV-infected persons, a few surveys [7,8] found a much lower prevalence. This divergence of results is thought to arise from a difference in the conformation of the E2 protein utilized in the antibody detection system; some researchers [3][4][5] used glycosylated undenatured E2 protein, but others [7,8] used nonglycosylated or denatured protein.…”
mentioning
confidence: 91%
See 2 more Smart Citations